Pengaruh Beban Kerja Terhadap Kelelahan Kerja (Studi Kasus pada Karyawan PT. Adira Dinamika Multi Finance Cabang Muara Bungo) - Ratumas Hartha Delima (Universitas Batanghari Jambi, 2018)
The purpose of this study was to determine how the influence of workload on work fatigue collection and marketing at PT. Adira Dinamika Multi Finance, Muara Bungo. The independent variable is the workload and the dependent variable is work fatigue. This type of research is a quantitative approach. The scale of measurement of variables in this study is using Likert scale. In this study the population is the collection and marketing employees at PT. Adira Dinamika Multi Finance, Muara Bungo which amounted to 32 people. Data analysis method in this research use simple linear regression. Based on the results of data processing, partial test results of workload variables on work fatigue have t-count> t-table of 9.706> 2.042, then the decision is Ho rejected and Ha accepted means that the workload variable has an effect on employee fatigue part collection and marketing at PT. Adira Dinamika Multi Finance, Muara Bungo. Thus the higher the workload given the company will increase employee fatigue. The result of determination test (R2) can be concluded that having the ability of work load variable to explain the variation of employee fatigue variable is 75,8%. This shows that the work fatigue of employees of a company can increase if the workload given by the company is high. For 24.2% can be explained by other factors outside of this study.